Balance, gait, functionality and strength: comparison between elderly fallers and non-fallers - Cebolla, Elaine C. (Braz J Phys Ther, 2015)
BACKGROUND: Accidental falls are a major health problem related to aging and affect one in every three elderly individuals over the age of sixty. OBJECTIVE: To evaluate and compare the muscle strength, gait kinematics parameters, and performance in functional tests between elderly subjects with and without a prior history of falls. In addition, the association between the history of falls and the variables that demonstrated differences between groups were tested. METHOD: 62 elderly subjects participated in the study and were allocated to the group with falls history (FG; n=20; 68.0±6.9 years old) or the group without falls history (CG; n=42; 65.5±4.1 years old). Maximal strength, gait kinematics parameters, and functional tests were tested. RESULTS: The FG showed lower muscle strength in the knee flexors (51.45±8.6 vs. 62.09±19 Kg), lower average toe clearance during the swing phase (0.04±0.006 vs. 0.043 ± 0.005 m), and lower performance in the "8-foot up-and-go" test (5.3±0.7 vs. 5.8±0.7 s) (p<0.05). There were no associations between any variables and falls, but the increased time in the "8-foot up-and-go" test may double the likelihood of a fall occurring. CONCLUSION: Fallers have reduced lower limb strength, gait alterations, the worst performance in the dynamic balance test, and an increased risk of falls.